Analysis of Coulomb Stress Changes in Aceh Earthquake on Sibayak Volcano - Goldberd Harmuda Duva Sinaga; Agoez Loeqman; Ruben Cornelius Siagian; Mardame Pangihutan Sinaga (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
Based on geological conditions, Indonesia is located between the Indo-Australian plate, the Eurasian plate, and the Pacific plate, making Indonesia prone to tectonic earthquakes. However, since the big earthquake that occurred in Aceh on December 26, 2004, the geological conditions in Sumatra have undergone significant changes marked by stressful situations in the western to southern regions of Sumatra, especially on Sibayak Volcano. This study used data from BMKG and Global CMT, which included magnitude (Mw), depth, earthquake coordinates (longitude and latitude), type of earthquake, strike, dip, and rake. From the analysis using Coulomb 3.3, the highest coulomb stress value of Sibayak Volcano was obtained in 2015 with an average change in coulomb stress of 0.235 bar, shear 0.1909 bar, normal 0.1106 bar. However, the lowest coulomb stress value occurs in 2021 with a moderate shift in coulomb stress of 0.0593 bar, shear 0.0251, normal 0.0849 bar.